Multisource feedback: An overview of its use and application as a formative assessment - Lockyer, Jocelyn; Sargeant, Joan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Multisource feedback (MSF), often termed 360-degree feedback, is a formative performance assessment in which data about an individual’s observable workplace behaviors are collected through questionnaires from those interacting with the individual; data are aggregated for anonymity and confidentiality; the aggregated data, along with self-assessment if available, are provided to the individual; and the recipient meets with a trusted individual to review the data and develop an action plan. It is used along the continuum of medical education. This article provides an overview of MSF’s utility, its evidence base and cautions.